Evaluation of Multi-Jurisdictional Task Forces in the United States, 1999-2000 - Hayeslip, David W. ([Verlag nicht ermittelbar], 2004)
Since the inception of the Edward Byrne Memorial State and Local Law Enforcement Assistance Program in 1988, a large proportion of formula grant program funds has been allocated by state administrative agencies (SAA) to support multi-jurisdictional drug task forces (MJTFs). MJTFs are a subset of law enforcement task forces that were created in order to target the illegal distribution of drugs at the local and regional levels. While many policymakers, researchers, and practitioners express confidence in the task force approach generally, there remains insufficient understanding of the possible community and organizational impact of individual MJTFs and the kinds of evaluation methodologies that can elicit such information. The goal of this project was to identify several methodologies that could be used by state planning agencies, task forces, and others to assess the work of MJTFs. This project consisted of two surveys that were designed to ascertain the extent to which state administrative agencies (SAAs) and multi-jurisdictional drug task forces (MJTFs) collected various kinds of process and outcome information and conducted evaluations of task forces.